Effect of position and height of a shield on convective heat transfer performances of plate fin heat sink - Bouchenafa, Rachid; Saim, Rachid; Abboudi, Said; Öztop, Hakan Fehmi (Emerald Group Publishing Ltd, 2015)
Purpose - The purpose of this paper is to examine the thermal and dynamic performance of the plate-fin heat sink fitted with a shield in the bypass. Design/methodology/approach - The governing equations were solved using the finite volume method based on the SIMPLE algorithm. The k-omega Shear Stress Transport was used to model turbulence. The thermal and dynamic results were presented in term of average Nusselt number and friction factor, respectively. The effect of the height (Hs = 6, 10 and 13) and the position (X = 0, 1/3, 1/2, 2/3 and 3/4) of the shield was studied for a Reynolds number ranging from 2 x 10(3) to 12 x 10(3) and compared with a heat sink without shield. To evaluate the performance of different heat sink geometries, the efficiency was presented and discussed. Findings - By adding a shield in the bypass, a greater amount of air is injected between the heat sink fins, which improves the heat transfer (advantage) of the one part, and increases the friction on the other hand (disadvantage). The efficiency of the heat sink varies inversely proportional with the Reynolds number. Originality/value - The originality of this work is the method for enhancement of heat transfer.
Keywords: Turbulence; Finite volume; Bypass; Forced convection; Heat sink; Shield